Gas-phase synthesis of Mg–Ti nanoparticles for solid-state hydrogen storage. Issue 1 (25th November 2015) - Calizzi, M.; Venturi, F.; Ponthieu, M.; Cuevas, F.; Morandi, V.; Perkisas, T.; Bals, S.; Pasquini, L.
Abstract : The structure of Mg–Ti nanoparticles and their hydrogen sorption properties are studied for different Ti contents. The metastable Mg–Ti solid solution formed in the as-prepared state decomposes upon H-absorption, leading to a MgH2 /TiH2 nanocomposite with very fast H-sorption kinetics. Abstract : Mg–Ti nanostructured samples with different Ti contents were prepared via compaction of nanoparticles grown by inert gas condensation with independent Mg and Ti vapour sources. The growth set-up offered the option to perform in situ hydrogen absorption before compaction. Structural and morphological characterisation was carried out by X-ray diffraction, energy dispersive spectroscopy and electron microscopy. The formation of an extended metastable solid solution of Ti in hcp Mg was detected up to 15 at% Ti in the as-grown nanoparticles, while after in situ hydrogen absorption, phase separation between MgH2 and TiH2 was observed. At a Ti content of 22 at%, a metastable Mg–Ti–H fcc phase was observed after in situ hydrogen absorption. The co-evaporation of Mg and Ti inhibited nanoparticle coalescence and crystallite growth in comparison with the evaporation of Mg only. In situ hydrogen absorption was beneficial to subsequent hydrogen behaviour, studied by high pressure differential scanning calorimetry and isothermal kinetics. A transformed fraction of 90% was reached within 100 s at 300 °C during both hydrogen absorption and desorption. The enthalpy of hydride formation was not observed to differ from bulk MgH2 .